A new species of Platanthera (Orchidaceae, Orchideae) from southeast of Xizang, China - Lin, Dongliang; Li, Jianwu; Ye, Chao; Wen, Haixia; Jin, Xiaohua (Phytotaxa, 2024)
A new species of orchid, Platanthera medogensis, was described and illustrated from Xizang Autonomous Region, China. P. medogensis is close to P. bakeriana and P. chiloglossa, but is readily distinguished from the latter by having ovate-lanceolate lip concave at base with two calli, linear visidium, two stigmas below the rostellum. Molecular phylogenetic analysis based on five markers (nrITS, matK, psbA-trnH, rbcL, trnL-F) revealed that P. medogensis is sister with P. exelliana by full support.